2018
DOI: 10.1071/fp17195
|View full text |Cite
|
Sign up to set email alerts
|

Wheat pre-anthesis development as affected by photoperiod sensitivity genes (Ppd-1) under contrasting photoperiods

Abstract: Fine tuning wheat phenology is of paramount importance for adaptation. A better understanding of how genetic constitution modulates the developmental responses during pre-anthesis phases would help to maintain or even increase yield potential as temperature increases due to climate change. The photoperiod-sensitive cultivar Paragon, and four near isogenic lines with different combinations of insensitivity alleles (Ppd-A1a, Ppd-B1a, Ppd-D1a or their triple stack) were evaluated under short (12 h) and long (16 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
(90 reference statements)
6
15
0
Order By: Relevance
“… Miglietta, 1989 ; Slafer and Rawson, 1994 b ), disregarding whether the length of the phase was determined in thermal time or in phyllochrons. This is because, in agreement with previous studies, the rate of appearance of early leaves seems insensitive to photoperiod ( Slafer and Rawson, 1997 ) and unaffected by photoperiod insensitivity genes ( González et al , 2005 ; Ochagavía et al , 2017 ), although exceptions can be found, at least when grown in controlled conditions ( Pérez-Gianmarco et al , 2018 ). This parallelism is the main reason why the effects of daylength and/or photoperiod insensitivity genes on wheat development can frequently be estimated through their effects on FLN (e.g.…”
Section: Discussionsupporting
confidence: 91%
“… Miglietta, 1989 ; Slafer and Rawson, 1994 b ), disregarding whether the length of the phase was determined in thermal time or in phyllochrons. This is because, in agreement with previous studies, the rate of appearance of early leaves seems insensitive to photoperiod ( Slafer and Rawson, 1997 ) and unaffected by photoperiod insensitivity genes ( González et al , 2005 ; Ochagavía et al , 2017 ), although exceptions can be found, at least when grown in controlled conditions ( Pérez-Gianmarco et al , 2018 ). This parallelism is the main reason why the effects of daylength and/or photoperiod insensitivity genes on wheat development can frequently be estimated through their effects on FLN (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…There was a direct effect of photoperiod on time to anthesis, that was not restricted to the phase from seedling emergence to TS as the LRP was also affected by the exposure to contrasting day lengths (in line with previous evidences in the literature showing that the LRP can be highly sensitive to photoperiod; González et al, 2005bGonzález et al, , 2003Pérez-Gianmarco et al, 2018). As NILs had the insensitive allele for Ppd-D1 gene (Ppd-D1a),…”
Section: Discussionsupporting
confidence: 74%
“…However, the NILs would have sensitive alleles in the Ppd-1 loci on A and/or B genome. These genes produce responses that are frequently less noticeable than Ppd-D1, but still significant (Bentley et al, 2011;Pérez-Gianmarco et al, 2018;Shaw et al, 2013Shaw et al, , 2012. Again as expected from the literature, photoperiod effects on the rate of phenological development is not paralleled by concomitant effects on the rate of leaf initiation and therefore the final number of leaves was increased under short days (Slafer and Rawson 1994b).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations